2014
DOI: 10.36045/bbms/1414091004
|View full text |Cite
|
Sign up to set email alerts
|

Differences of Quermass- and Dual Quermassintegrals of Blaschke-Minkowski and Radial Blaschke-Minkowski Homomorphisms

Abstract: In this article, we establish Minkowski, Brunn-Minkowski and Aleksandrov-Fenchel type inequalities for differences of quermass-and dual quermassintegrals of mixed Blaschke-Minkowski and mixed radial Blaschke-Minkowski homomorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Regarding the studies of the (mixed) radial Blaschke-Minkowski homomorphisms, many results have been found in the previous studies, see, e.g., [5][6][7][9][10][11][12][13][14][15][16][17][18]20].…”
Section: Introduction and Main Resultsmentioning
confidence: 93%
“…Regarding the studies of the (mixed) radial Blaschke-Minkowski homomorphisms, many results have been found in the previous studies, see, e.g., [5][6][7][9][10][11][12][13][14][15][16][17][18]20].…”
Section: Introduction and Main Resultsmentioning
confidence: 93%
“…This gives inequality (6). In addition, equality holds in inequality (6) if and only if L 1 and L 2 are dilates.…”
Section: Lemma 32 ([24]mentioning
confidence: 90%
“…From this, inequality Equation (25) is obtained. By the equality conditions of Equation (24) and the Minkowski integral inequality, we see that equality holds in Equation (25) if and only if K and L are dilated.…”
Section: Brunn-minkowski Inequalities For the L P Radial Blaschke-minmentioning
confidence: 94%
“…Meanwhile, associated with L p radial Blaschke-Minkowski homomorphisms, Wang et al [23] extended Schuster's results including the Busemann-Petty Problem 2. In recent years, a lot of important conclusions for the radial Blaschke-Minkowski homomorphisms and their L p analogies were obtained (see e.g., [22][23][24][25][26][27][28][29][30][31][32][33]).…”
mentioning
confidence: 99%